2019
DOI: 10.1097/lgt.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

Fact or Fiction? Adipose-Derived Stem Cells and Platelet-Rich Plasma for the Treatment of Vulvar Lichen Sclerosus

Abstract: Objective The aim of the study was to summarize and review the evidence for the efficacy and safety of adipose-derived stem cells (ADSCs) and platelet-rich plasma (PRP) for the treatment of vulvar lichen sclerosus (LS). Materials and Methods PubMed/MEDLINE, Ovid, Web of Science, and clinicaltrials.gov were searched from inception up to May 7, 2018. Results Seven observational studies were identified, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 17 publications
0
29
0
2
Order By: Relevance
“…Similarly, platelet-rich plasma (PRP) therapy acts as a regenerative agent as it has tissue factors for cell growth, migration, repair, proliferation, and regeneration. It is still in experimental stages with few reports of successful management of patients with VLS [39]. Prospective randomized trials are needed to provide an evidence base for this therapy.…”
Section: Role Of Adipose-derived Stem Cells and Platelet-rich Plasma mentioning
confidence: 99%
“…Similarly, platelet-rich plasma (PRP) therapy acts as a regenerative agent as it has tissue factors for cell growth, migration, repair, proliferation, and regeneration. It is still in experimental stages with few reports of successful management of patients with VLS [39]. Prospective randomized trials are needed to provide an evidence base for this therapy.…”
Section: Role Of Adipose-derived Stem Cells and Platelet-rich Plasma mentioning
confidence: 99%
“…Sporadic data in the literature reported that the application of lipofilling and autologous (PRP) are effective for the therapeutic management of LS 18‐23,43‐46 . The simultaneous use of lipofilling and PRP has been previously reported in a single case report and in a study including 15 female LS patients lacking a control group of patients treated only with lipofilling in comparison to the combinatory therapy 18,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Casabona et al in 2010 first described the use of homologous fat grafting and platelet‐rich plasma (PRP) in LS treatment to reduce atrophy and scarring and improve skin tropism 18 . Then, other groups reported successful treatment of LS patients using fat grafting, stromal vascular fraction (SVF) enriched fat grafting, or purified adipose‐derived stem cells 19‐23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPRP for MGLSc has been advocated to be a safe and effective option; however, no prospective studies have yet been done in men 7,8 . The putative mechanism is promoting healthy tissue formation by releasing growth factors; an analgesic role has also been postulated 9‐12 …”
Section: Introductionmentioning
confidence: 99%